Exploring Carbon-Based Derivative Electrodes for Voltammetric Detection of Profenofos Pesticide in Environment: A Review - Edihar, Muh; Zulkarnaen, Muhammad Aryo; Salim, La Ode Agus (CV. Science Tech Group, 2024)
Detection and monitoring of pesticide residues in the environment have become crucial due to their potential adverse effects on human health and ecosystems. Among these pesticides, Profenofos has garnered primary attention due to its widespread usage and persistence in agricultural practices. Voltammetric techniques offer a promising approach for sensitive and selective detection of Profenofos, with carbon-based derivative electrodes emerging as highly promising candidates. This review critically examines recent advancements in the utilization of carbon derivative electrodes for Profenofos detection via voltammetry. It explores the fundamental principles, fabrication methods, and performance characteristics of these electrodes, highlighting their strengths and limitations. Additionally, the review discusses strategies for enhancing the sensitivity, selectivity, and stability of carbon derivative electrodes, as well as their potential application in environmental monitoring and agricultural practices. Through a comprehensive synthesis of recent research findings, this review aims to provide valuable insights into the current status, challenges, and future directions in the field of Profenofos pesticide detection using carbon derivative electrodes and voltammetric techniques.